2012
DOI: 10.1063/1.3688219
|View full text |Cite
|
Sign up to set email alerts
|

The coexistence of two-dimensional electron and hole gases in GaN-based heterostructures

Abstract: The formation of two-dimensional carrier gases in gated GaN/AlGaN/GaN heterostructures is investigated theoretically. It is shown that under certain conditions a two-dimensional hole gas at the upper GaN/AlGaN interface can be formed in addition to the two-dimensional electron gas at the lower AlGaN/GaN interface. For the calculations, a Schrdinger-Poisson solver and a simple analytical model developed in the present work are used. Conditions for the formation of a two-dimensional hole gas are elaborated. It i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…This has been confirmed experimentally [7] and by the simulations [8]. In the n-channel HEMT, this coexistence is not always desirable and mostly should be avoided as it might shield the 2DEG channel from the gate [8].…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…This has been confirmed experimentally [7] and by the simulations [8]. In the n-channel HEMT, this coexistence is not always desirable and mostly should be avoided as it might shield the 2DEG channel from the gate [8].…”
Section: Introductionmentioning
confidence: 66%
“…This has been confirmed experimentally [7] and by the simulations [8]. In the n-channel HEMT, this coexistence is not always desirable and mostly should be avoided as it might shield the 2DEG channel from the gate [8]. However, with the assistance of the GaN cap electric field distribution can be made uniform at the drain-side of the gate leading to an increase in breakdown voltage [9].…”
Section: Introductionmentioning
confidence: 85%
“…The device architecture is optimized to obtain a normally-off (the enhancement mode operation) transistor by increasing the GaN cap thickness from 2 nm to 15 nm, 20 nm, 25 nm, 30 nm and 35 nm in the 1 µm gate length GaN/Al 0.25 Ga 0.75 N/GaN/Al 0.075 Ga 0.925 N/Al 0.1 Ga 0.9 N MIS-HEMT but the SiN passivation layer is reduced to 5 nm [40]. However, a two-dimensional hole gas (2DHG) exists between the GaN cap layer and the AlGaN barrier alongside the 2DEG when the cap layer increases more than 10 nm [41]. As the GaN cap thickness is increased, the AlGaN barrier is kept at the same thickness of 20 nm.…”
Section: Proposed Enhancement Mode Gan Mis-hemtsmentioning
confidence: 99%
“…We see also an increase in the drain current from 40 mA/mm when using the 15 nm GaN cap to 60 mA/mm when using the 35 nm cap. It was reported that increasing the thickness of GaN cap layer would reduce the electron density in 2DEG channel [41].…”
Section: The Impact Of Gan Capmentioning
confidence: 99%
“…Furthermore, during the theoretical study of metal-AlGaN/GaN heterostructure, Singh et al predicted that the large band bending and degenerate 2DEG induced by the polarization charges at the undoped AlGaN/GaN heterointerface makes possible a new type of TJ with tailored tunneling probabilities and current-voltage (I–V) characteristics 14 15 . Theoretically, for a GaN/AlGaN/GaN heterostructure, a two-dimensional hole gas (2DHG) also can be induced at the upper GaN/AlGaN heterointerface with the similar carrier concentration as that of 2DEG at the lower AlGaN/GaN heterointerface 16 . The simultaneous appearance of degenerate polarization-induced 2DEG and 2DHG in GaN/AlGaN/GaN heterostructure can enable interband tunneling process.…”
mentioning
confidence: 99%